2020
DOI: 10.3934/publichealth.2020053
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cancer in Saudi Arabia thru 2010–2019: a systematic review with constrained meta-analysis<span style="font-size: 12px"> Running title: epidemiology of cancer in Saudi Arabia thru 2010–2019</span>

Abstract: Background Cancer is emerging as a major global health-care system challenge with a growing burden worldwide. Due to the inconsistent cancer registry system in Saudi Arabia, the epidemiology of cancer is still dispersed in the country. Consequently, this review aimed to assemble the epidemiological metrics of cancer in Saudi Arabia in light of the available published data during the period from (2010–2019). Methods Published literature from Saudi Arabia relating to canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 56 publications
1
85
0
Order By: Relevance
“…3 , 28 A significant geographical variation in the incidence of thyroid cancer throughout the KSA was documented in 2013. 5 This geographical variation pointed to different risk factors contributing to thyroid cancer: nutritional patterns, together with excessive weight gain, 39 high consumption of processed chicken and fresh and processed fish products 25 and environmental carcinogens, such as pollutants and radiation exposure. 24 Furthermore, the differences in the genetic backgrounds of the study groups and the polygenetic factors – activation of oncogenes such as Rat sarcoma (RAS), human gene that encodes a protein called B-Raf (BRAF), receptor tyrosine kinase/phenylthiocarbamide (RET/PTC) and the overstimulation of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) pathway – are involved in thyroid tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 , 28 A significant geographical variation in the incidence of thyroid cancer throughout the KSA was documented in 2013. 5 This geographical variation pointed to different risk factors contributing to thyroid cancer: nutritional patterns, together with excessive weight gain, 39 high consumption of processed chicken and fresh and processed fish products 25 and environmental carcinogens, such as pollutants and radiation exposure. 24 Furthermore, the differences in the genetic backgrounds of the study groups and the polygenetic factors – activation of oncogenes such as Rat sarcoma (RAS), human gene that encodes a protein called B-Raf (BRAF), receptor tyrosine kinase/phenylthiocarbamide (RET/PTC) and the overstimulation of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) pathway – are involved in thyroid tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…37 Interestingly, our results and result of literature review study showed almost similar findings regarding the benign, Bethesda III-VI, and the 38 The high prevalence of Bethesda III-VI might be explained by the global increase of thyroid cancer, 1,2 in gulf countries 3,4 and in KSA. 5,27,39 Moreover, this could be explained by the improvement of high-quality ultrasounds and screening for thyroid nodulesenhancing detection and diagnosis of thyroid cancers -and a possible increase in exposure to risk factors. 3,28 A significant geographical variation in the incidence of thyroid cancer throughout the KSA was documented in 2013.…”
Section: Discussionmentioning
confidence: 99%
“…An expanded retrospective analysis of CNS tumors has never been conducted in Saudi Arabia. Only a single constrained retrospective analysis of cancer incidence was performed in the Eastern population of Saudi Arabia, and another general meta-analysis was performed that estimated brain cancer to account for 9.5% of all cancer diagnoses [ 6 ]. In the current study, we performed a retrospective analysis of CNS tumors in the Western Province of Saudi Arabia in the period 2014-2019.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, breast cancer is the predominant type of cancer with an overall incidence rate of 14.8% among both genders, accounting for 29.7% of cancer among females. Moreover, the breast cancer mortality rate in Saudi Arabia was estimated at 8.5% of all cancer-related deaths [ 3 ].…”
Section: Introductionmentioning
confidence: 99%